Exploring primary care health professionals’ perceived influence of their communication on HPV vaccine acceptance: Results from a national survey - Olufeyisayo O. Odebunmi; Anna Ilyasova; Assanatou Bamogo; Yeshaben Patel; Colleen Higgins; Erin Laurie; Lisa N. Mansfield; Sachiko Ozawa; Stephanie B. Wheeler; Lisa P. Spees (PLoS ONE, 2026)
Objective To evaluate primary care health professionals’ (PCHPs) perspectives on how their communication influences HPV vaccine acceptance, based on the self-perception theory. And to examine the factors associated with PCHPs’ perceived influence on HPV vaccine acceptance. Methods An online national survey was administered between May and July 2022 to PCHPs involved in HPV vaccination for children ages 9–12 years old. Survey items comprised of PCHPs’ demographics, clinic settings, and selected HPV communication measures, such as influence of vaccine communication, strategies and challenges, and past HPV vaccine communication training. Logistic regression models assessed factors associated with PCHPs’ perceived influence of their communication on HPV vaccine acceptance. Results The majority of PCHPs felt their communication greatly influenced HPV vaccine acceptance. Compared to PCHPs who thought that communication had little or some influence on HPV vaccine acceptance, PCHPs who thought their communication greatly influenced HPV vaccine acceptance were more likely to: 1) use presumptive recommendations (aOR: 1.32; 95% CI: 1.11, 1.57), 2) report parental concerns about HPV vaccination promoting sexual activity (aOR:1.26, 95% CI: 1.06, 1.51), and 3) have had HPV vaccine communication training on how to address parental HPV vaccine hesitancy (aOR:1.25; 95% CI: 1.02, 1.54). Conclusion This study demonstrates the pivotal role of vaccine communication in influencing HPV vaccine acceptance among PCHPs. Tailored vaccine communication training that involves the entire primary care team and equips them with effective communication techniques is essential to increase PCHP’s confidence in vaccine conversations and competence in making HPV vaccine recommendations. HPV vaccine communication should also include content that promotes the cancer preventive role of HPV vaccine and debunks the myth around HPV vaccination promoting sexual activity.